Laparoscopic Duodenojejunostomy for the SMA Syndrome - Ehlers, Till-Oliver; Tsamalaidze, Levan; Pereira, Lucio; Stauffer, John (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2018)
Objective The Superior Mesenteric Artery Syndrome (SMAS) was first described by Rokitansky in 1842. Clinical symptoms include postprandial pain, nausea, vomiting and weight loss. Duodenojejunostomy is the treatment of choice for patients with SMAS. We now present a case of a young female with SMAS who successfully underwent laparoscopic duodenojejunostomy.Indications The first line treatment for SMAS is medical management, which includes infusion therapy, bowel rest, parenteral nutrition and a nasojejunal feeding tube inserted into the jejunum past the obstruction. If medical therapy fails, surgery is recommended.Procedure A symptomatic patient with body mass index (BMI) of 19.4 kg/m2 underwent laparoscopic duodenojejunostomy. The patient tolerated the procedure well. The post-operative period was uneventful and the patient was discharged after three days. On six month follow up, the patient had gained weight and her symptoms were completely resolved.Conclusion SMAS is still a poorly recognised pathology. A high index of suspicion should be given for patients with unclear causes of postprandial nausea, vomiting and abdominal pain, especially in young females. A laparoscopic approach seems to be safe and effective for patients with SMAS.
Keywords: SMA syndrome; duodenojejunostomy; laparoscopy